Design and analysis of Three-Axis Piezoresistive accelerometer - Suraya Abdullah (Universiti Malaysia Perlis, 2008)
Recently, micro-electromechanical system (MEMS) technologies have been used to manufacturer accelerometers. MEMS sensors include tranducers elements and the necessary signal conditioning electronics integrated together on a single integrated circuit (IC). This report describes several types of MEMS accelerometer at the beginning. However, the design is focused on a three-axis piezoresistive accelerometer. The accelerometer consists of a highly symmetric single-crystalline silicon crossbeam structure with 12 conventional piezoresistive implants in the beam. The piezoresistive accelerometer is designed and analyzed using MEMSPro v5.1 and Oofelie v2.2. The simulation results from finite element analysis are compiled and discussed. There have been several approaches in this design which are small size, large displacement and consume less power. Various types of these miniaturized accelerometers are increasingly being applied in different kind of portable micro-system such as biomedical application, and motion control system because of their extremely small size, which allow for easy installment in inaccessible areas or on small electronics assemblies. However, the simulation results will be taken which is consists of different dimension and parameters at the end of projects.